Ligand-based design and synthesis of N'-Benzylidene-3, 4-dimethoxybenzohydrazide derivatives as potential antimicrobial agents; evaluation by in vitro, in vivo, and in silico approaches with SAR studies. (31st December 2022) - Ezz Eldin, Rogy R.; Saleh, Marwa A.; Alotaibi, Mohammad Hayal; Alsuair, Reem K.; Alzahrani, Yahya A.; Alshehri, Feras A.; Mohamed, Amany F.; Hafez, Shaimaa M.; Althoqapy, Azza Ali; Khirala, Seham K.; Amin, Mona M.; A. F, Yousuf; et al.
Abstract: Herein, a series of N' -benzylidene-3, 4-dimethoxybenzohydrazide derivatives were designed and synthesised to target the multidrug efflux pump (MATE). The antibacterial activities were screened against S. aureus, Acinetobacter, S. typhi, E. coli, and P. aeruginosa, whereas their antifungal activities were screened against C. albicans . Compounds 4a, 4h, and 4i showed the most promising antibacterial and antifungal activities. Moreover, compounds 4h and 4i being the broader and superior members regarding their antimicrobial effects were selected to be further evaluated via in vivo testing using biochemical analysis and liver/kidney histological examination. Additionally, molecular docking was carried out to attain further deep insights into the synthesised compounds' binding modes. Also, ADMET studies were performed to investigate the physicochemical/pharmacokinetics features and toxicity parameters of the synthesised derivatives. Finally, a structure-antimicrobial activity relationship study was established to facilitate further structural modifications in the future. Highlights: A series of new N' -benzylidene-3, 4-dimethoxybenzohydrazide derivatives were designed and synthesised targeting the multidrug efflux pump (MATE) guided by the pharmacophoric features of the co-crystallized native inhibitor of the target protein. The newly synthesised compounds were assessed through in vitro, in vivo, and in silico approaches. Using the agar well diffusion assay, the antibacterial activities of the synthesised compounds were screened against S. aureus, Acinetobacter, S. typhi, E. coli, and P. aeruginosa, whereas, their antifungal activities were screened against C. albicans . The minimal inhibitory concentration (MIC) and the minimal bactericidal concentration (MBC) of the synthesised compounds were investigated on variable microbial species. Compounds (4h and 4i ) -as the broader and superior members regarding their antimicrobial effects- were further evaluated via in vivo testing using bio-chemical analysis and liver/kidney histological examination. A molecular docking study and ADMET in silico studies were performed. A structure-antimicrobial activity relationship study was established to facilitate further structural modifications in the future. Graphical Abstract: UF0001